Intestinal anti-inflammatory activity of coumarin and 4-hydroxycoumarin in the trinitrobenzenesulphonic acid model of rat colitis - Luchini, Ana Carolina [UNESP]; Rodrigues-Orsi, Patrícia [UNESP]; Cestari, Silvia Helena [UNESP]; Seito, Leonardo Noboru [UNESP]; Witaicenis, Aline [UNESP]; Pellizzon, Claudia Helena [UNESP]; Di Stasi, Luiz Cláudio [UNESP] (Pharmaceutical Society of Japan, 2008)
Coumarins represent an important class of phenolic compounds with multiple biological activities, including inhibition of lipidic peroxidation and neutrophil-dependent anion superoxide generation, anti-inflammatory and immunosuppressor actions. All of these proprieties are essential for that a drug may be used in the treatment of inflammatory bowel disease. The present study examined intestinal anti-inflammatory activity of coumarin and its derivative, the 4-hydroxycoumarin on experimental ulcerative colitis in rats. This was performed in two different experimental settings, i.e. when the colonic mucosa is intact or when the mucosa is in process of recovery after an initial insult. The results obtained revealed that the coumarin and 4-hydroxycoumarin, at doses of 5 and 25 mg/kg, significantly attenuated the colonic damage induced by trinitrobenzenesulphonic acid (TNBS) in both situations, as evidenced macroscopically, microscopically and biochemically. This effect was related to an improvement in the colonic oxidative status, since coumarin and 4-hydroxycoumarin prevented the glutathione depletion that occurred as a consequence of the colonic inflammation. © 2008 Pharmaceutical Society of Japan.
Keywords: 4-hydroxycoumarin; Colitis relapse; Coumarin; Rat colitis; 4 hydroxycoumarin; coumarin; glutathione; phenol derivative; salazosulfapyridine; superoxide; trinitrobenzenesulfonic acid; animal experiment; animal model; animal tissue; antiinflammatory activity; colon injury; colon mucosa; controlled study; drug dose comparison; enteritis; lipid peroxidation; male; neutrophil; nonhuman; oxidative stress; rat; treatment outcome; ulcerative colitis; 4-Hydroxycoumarins; Acute Disease; Alkaline Phosphatase; Animals; Anti-Inflammatory Agents; Chronic Disease; Colitis; Colon; Coumarins; Diarrhea; Gastrointestinal Agents; Glutathione; Male; Organ Size; Peroxidase; Rats; Rats, Wistar; Recurrence; Sulfasalazine; Trinitrobenzenesulfonic Acid